Automated Student Advising: An App for Greater Efficiency - Basan, Germaine E.; Esguerra, Joshze Rica L.; Lleva, Yrelle Mae R.; Calora, Patricia O. (International Journal on Open and Distance e-Learning, 2020)
One of the attributes of open and distance e-learning (ODeL) is its adoption and deployment of ICTs. This attribute sits at the very core of ODeL. Thus, quality in ODeL means adequate augmentation of its academic and administrative processes with innovative applications. To administer the conduct of student thesis in the ODeL context where there are many students, an efficient system of assigning research topics to appropriate thesis advisers is required. This paper documents the development and application for academic advising developed by the Faculty of Information and Communication Studies (FICS).